Enteric-coated mycophenolate sodium versus azathioprine in patients with active systemic lupus erythematosus: a randomised clinical trial. Issue 9 (27th April 2017) - Ordi-Ros, Josep; Sáez-Comet, Luis; Pérez-Conesa, Mercedes; Vidal, Xavier; Mitjavila, Francesca; Castro Salomó, Antoni; Cuquet Pedragosa, Jordi; Ortiz-Santamaria, Vera; Mauri Plana, Montserrat; Cortés-Hernández, Josefina
Abstract : Objective: To compare the efficacy and safety of enteric-coated mycophenolate sodium (EC-MPS) versus azathioprine (AZA) in patients with active systemic lupus erythematosus (SLE) disease. Methods: A multicentre, 24-month, superiority, open-label, randomised controlled trial (NCT01112215 ) was conducted with 240 patients (120 per arm) receiving either EC-MPS (target dose: 1440 mg/day) or AZA (target dose: 2 mg/kg/day) in addition to prednisone and/or antimalarials. The primary endpoint was the proportion of patients achieving clinical remission, assessed by SLE Disease Activity Index 2000 (SLEDAI-2K) and British Isles Lupus Assessment Group (BILAG), at 3 and 24 months. Secondary endpoints included time to clinical remission, BILAG A and B flare rates, time to flare, corticosteroid reduction and adverse events (AEs). Results: Proportion of patients achieving clinical remission (clinical SLEDAI=0) was higher in the EC-MPS group at 3 (32.5% vs 19.2%; treatment difference, 13.3 (CI 2.3 to 24), p=0.034) and 24 months (71.2% vs 48.3%; treatment difference, 22.9 (CI 10.4 to 34.4), p<0.001). EC-MPS was superior with respect to time to clinical remission (HR 1.43; 95% CI 1.07 to 1.91; p=0.017). BILAG A/B and B flares occurred more frequently in the AZA group (71.7% vs 50%, p=0.001 and 21.67% vs 8.3%, p=0.004, respectively). EC-MPS was superior with respect to time to first BILAG A/B (HR 1.81; 95% CI 1.3 to 2.56; p=0.0004) and BILAG A flare (HR 2.84; 95% CI 1.37 to 5.89; p=0.003). AEs were similar in both groups except for leucopenia that occurred more frequently with AZA. Conclusions: EC-MPS was superior to AZA in treating SLE and preventing further relapses. Trial registration number: NCT01112215; Results.